Predictive factors associated with short‐term mortality in cats with feline infectious peritonitis treated with remdesivir or GS‐441524 or both - Sho Goto; Tsuyoshi Kamiyoshi; Ryota Iwasaki (Journal of Veterinary Internal Medicine)
Abstract Background Although most cats with feline infectious peritonitis (FIP) respond to treatment with remdesivir or GS‐441524 or both with uneventful clinical courses, some die despite treatment. Objective Identify predictive factors associated with short‐term mortality in cats with FIP treated with IV remdesivir or PO GS‐441524 or both. Animals A total of 108 client‐owned cats with FIP. Methods Retrospective multicenter study using data collected from medical records. Factors associated with short‐term mortality, defined as death within 84 days, were identified. Univariate analysis a t‐test, Mann‐Whitney U test, or Fisher's exact test and multivariate logistic regression were performed to assess patient characteristics and clinicopathological variables between survivors and nonsurvivors. Results The short‐term mortality rate was 12.0% (95% confidence interval [CI], 6.6%‐19.7%). Univariate analysis identified plasma lactate dehydrogenase activity (LDH; P < .001) and bilirubin concentration (P = .001) as being significantly increased in nonsurvivors, whereas concentrations of albumin (P = .003), total protein (P = .03), sodium (P = .005), and potassium (P = .005) were significantly lower. Additionally, nonsurvivors were significantly less likely to be febrile (≥39.4°C; P = .006). Of these variables, only plasma LDH activity ≥323 U/L, a cut‐point determined by receiver operating characteristic curve analysis, was significantly associated with short‐term mortality by multivariate analysis (odds ratio, 15.30; 95% CI, 1.18‐198.00; P = .04). Conclusion Increased plasma LDH activity might be useful for predicting short‐term mortality, guiding monitoring, and establishing prognosis in cats with FIP.